Bestandsestimat og utbreiing av kvitryggspett Dendrocopos leucotos i Noreg - Stenberg, Ingvar (Ornis Norvegica, 2004)
Status and distribution of the White-backed Woodpecker Dendrocopos leucotos in Norway The White-backed Woodpecker, being classified as a vulnerable species in Norway, has declined dramatically in western Europe during the last decades. The primary reason is that forestry has removed dead deciduous trees with insect larvae, which constitutes its main food. At present, the only viable population in western Europe is found along the southern and western coast of southern Norway. Our responsibilities for a proper management of the species makes it important to know its status and distribution well. This is the main reason for the present paper, where the White-backed Woodpeckers historical and present distribution is described for each county. During the main survey of the species in Norway i.e. after 1985, it is reported during breeding from all counties in southern Norway except Hedmark, but only in autumn in northern Norway. The species is very scarce in the eastern part of the country, especially in the counties of Hedmark and Østfold, where only one nest is found after 1960. Hundred years ago it was relatively common in places in this area. Further west, in Oppland, its present distribution is very scattered, although it still may be breeding. During the last decades the decline of the species is best documented in the counties along the Oslofjord: Oslo-Akershus and Vestfold. Deciduous forest along watercourses and in hillsides were important habitats before most of these areas were clearfelled and planted with conifers. This also applies to the coastal areas of Telemark, but the species has fared better in the inner parts of this county, where today the only regular breeding population in eastern Norway is found. Although it is also a regular breeder in Aust-Agder, its distribution is somewhat scattered, in contrast to the very even occurence in most of Vest-Agder. Combined with favourable climatic condition, the steep terrain along fjords makes the forests along the western coast north to Trøndelag an optimal habitat for the species. The topography makes forestry avtivities difficult in many places, and the White-backed Woodpecker has a strong foothold, being somewhere the most common woodpecker species in the four counties of western Norway. It also breeds regularly in Trøndelag south of Trondheimsfjorden, but there are no evidences for breeding in northern Norway. Based on the present occurrence and densities of breeding pairs, the Norwegian population is estimated to about 1800 pairs.